Characterization of Profenofos Degrading Bacteria - Alina Akhdiya; Wartono Wartono; Eman Sulaeman; I Made Samudra (Jurnal AgroBiogen, 2018)
Bioremediation is an inexpensive, easy, and safe technology to rehabilitate agricultural land which is highly polluted with pesticides. The aims of this study were to isolate and characterize profenofos degrading bacteria isolated from Pangalengan soils. The isolation step was carried out by using spread plate method on Nitrate Mineral Salts (NMS) medium containing 100 ppm profenofos. The isolates were selected based on hypersensitive response (HR) and hemolytic test, and ability of the isolates to use and degrade profenofos. The selected isolates were characterized based on the sequence of 16 rRNA and detection of the α and β subunits of terminal deoxygenase and naphtalene dioxygenase encoded genes. Three isolates (CN26, CN44, and CN86), which could use profenofos as the exclusive C source, could degrade more than 86.75% profenofos containing growth medium. Based on the 16S rRNA sequences, the three isolates were closely related to Stenotrophomonas maltophilia (99%), Comamonas terrigena (99%), and Pseudomonas sp. (80%). Pseudomonas CN44 consistenly showed high profenofos degradation activity of up to 91.2% when grown on NMS medium (pH 6.8) for 72 hours. β subunit dioxygenase encoding gene of the isolates were detected using primers Rf2-F/Rf2-R, but optimation of PCR is still needed to detect the α subunit of the gene. Naphtalene dioxygenase gene was detected only from Pseudomonas CN44 using the primer pair 301f/1099r. Based on its biodegradation capability and molecular characteristics, Pseudomonas CN44 is very potential to be developed as a bioremediating agent of profenofos.